2016
DOI: 10.4137/idrt.s32162
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Point-of-Care Isothermal Amplification Assay for the Detection of Malaria without Nucleic Acid Purification

Abstract: Malaria remains one of the most prevalent infectious diseases and results in significant mortality. Isothermal amplification (loop-mediated isothermal amplification) is used to detect malarial DNA at levels of ~1 parasite/µL blood in ≤30 minutes without the isolation of parasite nucleic acid from subject’s blood or saliva. The technique targets the mitochondrial cytochrome oxidase subunit 1 gene and is capable of distinguishing Plasmodium falciparum from Plasmodium vivax. Malarial diagnosis by the gold standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…5, 6, 9, 12, 13 Sensitive detections of malaria parasites in these subpopulations, which are considered as important reservoirs of transmission, are particularly important for malaria elimination. 2, 12 Among various molecular amplification assays, loop-mediated isothermal DNA amplification (LAMP) has emerged as a promising technology for field use due to its simplicity, rapidness, sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…5, 6, 9, 12, 13 Sensitive detections of malaria parasites in these subpopulations, which are considered as important reservoirs of transmission, are particularly important for malaria elimination. 2, 12 Among various molecular amplification assays, loop-mediated isothermal DNA amplification (LAMP) has emerged as a promising technology for field use due to its simplicity, rapidness, sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, LAMP analysis is faster than qPCR because amplification can be accomplished without DNA extraction or using a crude lysate (Kostic et al, 2015; Modak et al, 2016). Previous studies demonstrated LAMP assays for quantification of Dehalococcoides spp.…”
Section: Introductionmentioning
confidence: 99%
“…LAMP assay can be completed within 1h, and its sensitivity is 10 to 100-fold higher than that of conventional Polymerase Chain Reaction (PCR) when purified DNA is used for the template [4]. As LAMP is performed using three pairs of specific primers for DNA amplification, its specificity is higher than that of PCR [7].…”
Section: Introductionmentioning
confidence: 99%
“…When sensitive differential diagnosis need to be achieved by LAMP assay, researchers normally use as template either genome DNA purified from blood or samples that have been boiled and roughly cleaned up by centrifugation [9,10]. Recently, Modak, et al reported that high-sensitive LAMP can be performed using blood samples that have been heated at 90˚C for 5 min to lyse blood cells and parasites, releasing target DNA as templates [4]. Because at least two (one to be set at 90˚C, another at 65˚C) heating blocks are necessary for high-throughput analysis by LAMP assay a considerable amount of electricity is required, which might be not abundant or easily available in rather deprived areas or basic health care environments where the test need to be performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation